2016
DOI: 10.1111/1750-3841.13217
|View full text |Cite
|
Sign up to set email alerts
|

Coalho Cheese Made with Protease from Thermomucor indicae‐seudaticae N31: Technological Potential of the New Coagulant for the Production of High‐Cooked Cheese

Abstract: The aim of this study was to explore the use of a new coagulant from Thermomucor indicae-seudaticae N31 for the manufacture of a high-cooked starter-free cheese variety, by evaluating its physicochemical and functional characteristics in comparison to cheeses made with a traditional commercial coagulant. Coalho cheese was successfully produced with the new protease as it exhibited comparable characteristics to the one produced using the commercial enzyme: pH behavior during manufacture; cheese composition; pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Thermomucor is a recently reported genus in Daqu , and is reported to be one of the main genera of eukaryotic microorganisms in Maotai flavour and strong flavour Daqu . Although this genus has received little attention and no studies have reported its role in Daqu , its members are known to be thermoduric organisms capable of producing glucoamylase, glucosidase, cellulase, xylanase, lipase and protease . Therefore, it possible that this genus may play a role in the saccharification of Daqu .…”
Section: Resultsmentioning
confidence: 99%
“…Thermomucor is a recently reported genus in Daqu , and is reported to be one of the main genera of eukaryotic microorganisms in Maotai flavour and strong flavour Daqu . Although this genus has received little attention and no studies have reported its role in Daqu , its members are known to be thermoduric organisms capable of producing glucoamylase, glucosidase, cellulase, xylanase, lipase and protease . Therefore, it possible that this genus may play a role in the saccharification of Daqu .…”
Section: Resultsmentioning
confidence: 99%
“…[20,30,32] Interestingly, Thermomucor, which has been found in Daqu in only a few studies, can secrete large amounts of various hydrolyzing enzymes, including protease, glucosidase, glucoamylase, lipase, and pectinase, which can decompose macromolecules. [28,[33][34][35][36][37][38][39] Thermomucor is therefore expected to be an important contributor to the saccharification and liquefication activities and to cause small metabolites and volatile compounds to be produced during Baijiu production.…”
Section: Prokaryote Community Structure and Diversitymentioning
confidence: 99%
“…[41][42][43][44] As mentioned earlier, Thermomucor would have been one of the main contributors of the saccharification and esterification activities because it can produce glucoamylase, glucosidase, lipase, pectinase, protease, and other enzymes. [34,35,38,39] It has been found in some studies that Lichtheimia is strongly saccharogenic and causes starch hydrolysis. [45] It has also been found that these biota can produce esterase or lipase, which can give high esterification activities.…”
Section: Relationships Between Physicochemical Properties and Microbimentioning
confidence: 99%
“…Subsequently, a new investigation using this peptidase from T. indicae-seudaticae N31 evaluated the manufacture of a high-cooked starter-free cheese variety, whose physicochemical and functional properties were similar to those of the commercial coagulants [99].…”
Section: Thermophilic Proteolytic Enzymesmentioning
confidence: 99%